2015
DOI: 10.1177/1203475415612422
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the PlasmaBlade and Acellular Dermal Matrix in Rhinophyma Surgery

Abstract: We offer a new approach to surgical treatment of rhinophyma. Total excision of phymatous tissue and single session replacement of epidermal-dermal components is an effective treatment for patients with severe rhinophyma, resulting in satisfactory functional and aesthetic outcome. This combined treatment modality prevents the recurrence of rhinophyma. It should be considered an appropriate alternative in cases of severe rhinophyma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…ADMs have been used in craniofacial surgery to treat soft-tissue defects secondary to congenital conditions, disease and surgical wounds. 142 150 In aplasia cutis congenita (ACC), ADMs have shown utility both as an adjunct to grafting and as a conservative treatment for scalp coverage. 142 , 143 …”
Section: Resultsmentioning
confidence: 99%
“…ADMs have been used in craniofacial surgery to treat soft-tissue defects secondary to congenital conditions, disease and surgical wounds. 142 150 In aplasia cutis congenita (ACC), ADMs have shown utility both as an adjunct to grafting and as a conservative treatment for scalp coverage. 142 , 143 …”
Section: Resultsmentioning
confidence: 99%
“…A variety of other surgical interventions, such as the ultrasonic scalpel, disposable razor, PlasmaBlade, Versajet, or a combination of existing techniques, have also been attempted. However, there is no gold standard technique, and several factors, including size and location of the lesion, hemostasis, scar formation, procedure duration, and cost associated with each instrument must be taken into consideration [3,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors proposed ADM also for nasal reconstruction after rhinophyma surgery. In 2013 Selig et al described 5 cases of rhinophyma successfully treated by full-thickness excision and 1-step reconstruction by using Matriderm® and split-thickness skin graft [11]. In 2015 Özkan et al reported another case of rhinophyma treated with an electrosurgical device (PlasmaBlade) and single stage reconstruction with Matriderm® and split-thickness skin graft [12].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this large number of available techniques, total eradication is still considered in case of infiltrating rhinophyma, in the fibrous variant or rhinophyma with underlying skin cancer, and usually requires flap coverage or skin grafts [5]. In the last decade, some authors proposed the use of dermal substitutes for rhinophyma surgery, but only few case reports have been described throughout the Literature [[9], [10], [11]]. We described a new case of severe and disfiguring rhinophyma treated by total excision and acellular dermal matrix (ADM)-based reconstruction, with a 12-months postoperative follow-up.…”
Section: Introductionmentioning
confidence: 99%